Stercoral perforation of the normal colon: report of five cases - Velitchkov, Nadko (1996)
A series of five consecutive patients with stercoral perforation of the colon is presented. Four of the patients had free perforation and one had an abscess between the splenic flexure, spleen and surrounding organs, a yet unreported entity. All patients underwent emergency surgery including Iaparostomy with repeated explorations and lavages in two of them. The ethiology, pathophysiology and treatment of the condition are updated. A graphic algorithm for decision-making in appropriately dealing with stercoral perforation of the colon is proposed.